Reflective interventionist conversation analysis. Issue 6 (December 2020) - O'Reilly, Michelle; Kiyimba, Nikki; Nina Lester, Jessica; Muskett, Tom
A distinction has been drawn between basic (pure) conversation analysis (CA) and applied CA. Applied CA has become especially beneficial for informing areas of practice such as health, social care and education, and is an accepted form of research evidence in the scientific rhetoric. There are different ways of undertaking applied CA, with different foci and goals. In this article, we articulate one way of conducting applied CA, that is especially pertinent for practitioners working in different fields. We conceptualise this as Reflective Interventionist CA (RICA). We argue that this approach to applied CA is important because of its emphasis on the reflective stance that is valuable to an understanding of research data, its commitment to collaboration with practitioners, and its inductive style. In this paper, we outline the core premises and benefits of this approach and offer empirical examples to support our argument. To conclude, we consider the implications for evidence-based practice.